The expressive potential of the conceptualized words in Taras Shevchenko’s poetical speech (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article phenomenon of semantic transformation of lexeme «grave» is  considered in her vividly-conceptual use, co-operation of concepts KHATA / MOHYLA is interpreted as to the opposition binomial.
Keywords: concept; semantic structure of word; semantic transformation; connotation